TEACHERS’ PERSPECTIVES ON THE USE OF BUG’S LIFE BOARD GAME IN ENHANCING LINUS PUPILS’ VOCABULARYBOARD (Practitioner Research, 2019)
This action research aimed to explore the effectiveness of Bug’s Life Board Game in improving Year Four LINUS pupils’ vocabulary. LINUS pupils faced a lot of problems in learning L2 vocabulary because they failed to achieve constructs 2 to 12 in the LINUS screening tests. This paper reports the teachers’ perspectives on how The Bug’s Life Board Game affected their vocabulary teaching and students’ learning. This action research involved five cycles carried out over the duration of 2 months. Multiple methods of data collection such as pre-test and post- test, interview and teacher’s reflections were used to triangulate the findings. The results showed significant improvement in the pupils’ vocabulary and the teachers reported that Board Game created fun learning environment; increased students’ motivation to learn English vocabulary, developed creativity in designing materials for LINUS pupils and improved classroom management. It is recommended that games to be used in enhancing English vocabulary for remedial students in ESL context.